2019
DOI: 10.1088/1361-6641/ab3374
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of high quality sputtered III-nitride semiconductors and devices

Abstract: This article provides an overview of recent development of sputtering method for high-quality III-nitride semiconductor materials and devices. Being a mature deposition technique widely employed in semiconductor industry, sputtering offers many advantages such as low cost, relatively simple equipment, non-toxic raw materials, low process temperatures, high deposition rates, sharp interfaces, and possibility of deposition on large-size substrates, including amorphous and flexible varieties. This review covers t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 163 publications
0
20
0
Order By: Relevance
“…[1] In particular, AlInN alloys are special candidates for power electronics, highly efficient emitters, optoelectronic devices, and solar cells. [2][3][4][5][6][7][8] In that sense, radio-frequency (RF) magnetron sputtering allows the deposition of large-area and single-phase AlInN material using this low-cost and low-temperature technology exportable to the industry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1] In particular, AlInN alloys are special candidates for power electronics, highly efficient emitters, optoelectronic devices, and solar cells. [2][3][4][5][6][7][8] In that sense, radio-frequency (RF) magnetron sputtering allows the deposition of large-area and single-phase AlInN material using this low-cost and low-temperature technology exportable to the industry.…”
Section: Introductionmentioning
confidence: 99%
“…III‐Nitride semiconductors are interesting materials for the development of novel devices due to their direct bandgap energy tunable from the infrared (0.7 eV) for InN to the UV (6.2 eV) for AlN, their strong chemical and temperature endurance, and their radiation hardness . In particular, AlInN alloys are special candidates for power electronics, highly efficient emitters, optoelectronic devices, and solar cells . In that sense, radio‐frequency (RF) magnetron sputtering allows the deposition of large‐area and single‐phase AlInN material using this low‐cost and low‐temperature technology exportable to the industry.…”
Section: Introductionmentioning
confidence: 99%
“…To date, basic methods to fabricate various heterostructures for device applications are metal-organic vapor phase epitaxy, metal organic chemical vapor deposition and molecular beam epitaxy [1][2][3]. Many of these deposition techniques are difficult to apply over a large area and are expensive due to complexity of the apparatus used.…”
Section: Introductionmentioning
confidence: 99%
“…Although many research works on SAG-GaN NRs have been done in the past decade for MBE systems, study on MSE-SAG-GaN NRs is still limited due to the difficulty in handling liquid Ga sputtering source and in developing a proper nanopatterning process [34,35]. Magnetron sputter epitaxy (MSE) is a versatile NR growth technique with multiple distinct advantages, including easy integration on an industrial platform, reproducibility, smaller cost, and the absence of toxic precursors [35,36]. Previous works in a MBE-based system have shown that the effective Ga/N ratio is crucial to achieve high selectivity and high growth rate of SAG nanorods [15].…”
Section: Introductionmentioning
confidence: 99%